Sustainable Lipid-Based Drug Delivery: Development of Multiple Self-Emulsifying Systems for Hydrophilic Drugs Using Cashew Nut Oil - OYENIYI, Yinka James; Muhammed, Nura U (AlQalam Journal of Medical and Applied Sciences, 2025)
The oral delivery of hydrophilic drugs, such as 5-fluorouracil (5-FU), is often limited by poor permeability and rapid gastrointestinal degradation. Lipid-based self-emulsifying drug delivery systems (SEDDS) have shown promise in improving solubilization and oral bioavailability of lipophilic drugs; however, their application to hydrophilic molecules remains limited. This study aimed to develop multiple self-nanoemulsifying drug delivery systems (SNEDDS) for 5-FU using Cashew nut kernel oil (CKO) as a sustainable lipid excipient. A 2³ full factorial design evaluated the effects of CKO extraction method, oil-to-surfactant ratio, and homogenization speed on droplet size, polydispersity index (PDI), zeta potential (ZP), entrapment efficiency (EE%), and the cumulative drug release. Primary w/o emulsions were converted to w/o/w SNEDDS and solidified using Aerosil® 200, then encapsulated in hard gelatin capsules. Formulations JXM4 and JXM8 exhibited optimal characteristics with small droplet sizes (105 nm), low PDI (0.22), highly negative ZP (≥ −43 mV), low viscosity (< 70 cps), near-complete EE (> 98%), excellent flowability, and rapid self-emulsification. In vitro release studies showed >98% cumulative drug release within 60 minutes, while cytotoxicity assays (MTT) demonstrate effective anticancer activity with decreasing IC₅₀ values over 72 hours. Stability studies confirmed the preservation of physicochemical properties within acceptable limits over a 30-day period. These results indicate that optimized CKO-based SNEDDS can efficiently encapsulate hydrophilic drugs, providing a stable, sustainable, and orally administrable delivery platform. The study highlights the potential of regionally sourced lipids in enhancing the oral bioavailability of hydrophilic chemotherapeutics such as 5-FU and supports further in vivo investigations.